Professional Leadership Capabilities of Progressive Islamic Education Teachers - Ulul Albab; Aris Nurkhamidi; Ahmad Tarifin; Fatmawati Nur Hasanah; Abdulroya Panaemalae (Research Journal on Teacher Professional Development, 2023)
This study aims to analyze the professional abilities of progressive Islamic education leaders. By using literature research methods, this study shows that progressive Islamic education leadership capabilities must: 1) Involve the ability to develop a clear vision and strong educational mission, 2) The ability to inspire and motivate staff, students and other stakeholders. 3), Have good management skills, including resource management, strategic planning, and performance evaluation. 4) Have the ability to communicate effectively to be able to establish good relationships with all parties involved in educational institutions. Above all, an educational leader must have a strong commitment to student learning and development, as well as the ability to adapt to continuous changes in the world of education. These findings provide theoretical contributions in creating effective and sustainable educational leadership for Islamic educational institutions.